Strategic Social Marketing - French Jeff; Gordon Ross (Sage Publications, 2015)
This book takes a systemic approach to explaining the value of Marketing in solving social problems. The Importance of social Marketing for social policy, Marketing Social good, Strategic Social Marketing Systems thinking and Social Marketing, Research methods in Social Marketing, Critical Social.